Stroke Prevention in Atrial Fibrillation: Latest Clinical Trials and Guidelines - Luciana Armaganijan; Cristiano Dietrich; Dimpi Patel; Carlos A. Morillo (MDPI AG, 2012)
Atrial Fibrillation (AF) is the most common sustained arrhythmia and 1/6 strokes is attributed to AF. The cornerstone of treatment remains maintaining sinus rhythm or appropriate ventricular rate control in addition to prevention of stroke. Oral anticoagulation therapy (OAC) with vitamin K antagonists (VKAs) has been the gold standard for almost 50 years and a significant reduction in the risk of stroke in patients with AF has been demonstrated. Nonetheless, only 50% of patients with guideline recommendations for OAC treatment actually receive VKAs and half of these will discontinue therapy within 3 to 5 years with only another half achieving therapeutic ranges more than 50% of the time. The aforementioned limitations in addition with frequent blood monitoring have prompted the development of a series of new OAC therapies. The present review focuses on the current pharmacological management for stroke prevention in patients with AF based on current and emerging evidence.